Prioritizing the bottom line over people in a crisis: How leader behavior affects employee psychological distress under economic threat - Sofija Pajic; Claudia Buengeler; Deanne N. Den Hartog; Diana Hanke-Boer (PLoS ONE, 2025)
Aim This study examines the impact of direct supervisors’ leadership on employee psychological distress during crises. Specifically, it explores the relationship between people-oriented and bottom-line-mentality informed leader behaviors and employee psychological distress. The study further hypothesizes that employees’ sense of control functions as a psychological mechanism in this relationship and that this indirect effect is moderated by personal and national economic threat, both of which are particularly salient during crises. Method A quantitative survey was conducted in three waves among 854 employees across Europe (Germany, Italy, the Netherlands and Spain) during the COVID-19 pandemic, a highly salient global crisis. Results Findings indicate that employees with people-oriented leaders report lower psychological distress, mediated by an enhanced sense of control. In contrast, bottom-line-mentality informed leadership is associated with a diminished sense of control, and further with greater psychological distress. These effects are exacerbated under higher personal and national economic threat. Conclusion This study advances understanding of how constructive and destructive leadership behaviors influence employees’ psychological well-being during crises, particularly under economic strain. The findings provide actionable insights for leaders, organizations, and policymakers on mitigating employee psychological distress through leadership strategies that foster a sense of control.